Coupled Sine-Gordon Systems in DNA Dynamics. (15th May 2018) - Liu, Liya; Li, Chuanzhong
Abstract : We consider a model called the coupled sine-Gordon equation for DNA dynamics by introducing two double helix structures. The second double helix structure is unilaterally influenced by the first one. The completely integrable coupled sine-Gordon equation admits kink-antikink solitons with increased width representing a wide base pair opening configuration in DNA. Also we propose another coupled sine-Gordon model with variable coefficients for DNA dynamics under an inhomogeneous background. We find that the inhomogeneous DNA model has many interesting localized nonrational rogue wave solutions. We can find that the appearance of the rogue waves (possibly means the genetic mutation) in the nonlinear DNA model is highly related to the inhomogeneity.